The bilingual reading practices and performance of two Hispanic first graders - López-Velásquez, Angela M.; García, Georgia Earnest (Bilingual Research Journal, 2017)
This qualitative study used a sociocultural lens to examine how two bilingual Hispanic first-grade girls demonstrated bilingual reading practices (i.e., heteroglossia and translanguaging) as they discussed and read texts in Spanish and English. One girl predominantly received school reading instruction in Spanish, while the other received school reading instruction in English. They both participated in Spanish reading at home. The school reading instruction employed Spanish or English versions of Success for All, and emphasized word recognition strategies appropriate for the language of instruction along with meaning-making strategies. In April, the two girls scored mid- to end-of first grade on a curriculum-based reading assessment in the language of instruction. Neither of them received biliteracy instruction. Their reading levels in the instructional language and exposure to the other language appeared to be sufficient for them to develop and demonstrate heteroglossic practices. Bilingual dynamic reading assessments and home reading sessions with a bilingual researcher revealed that both girls utilized bilingual reading practices to discuss and comprehend texts in their non-instructional or alternate language. One of the girls also used bilingual reading practices to discuss texts in the instructional language. To read in the alternate language, they both employed word-recognition and meaning-making strategies, which had been emphasized in their school reading instruction. However, one girl’s attempt to use a decoding strategy she had learned in English (i.e., onset-rime) to decode unfamiliar Spanish words did not work effectively. Implications are delineated for the bilingual reading instruction and assessment of young bilingual children.
Keywords: dept.sed

Exploring English and Spanish rhyme awareness and beginning sound segmentation skills in prekindergarten Spanish-speaking English Learners - Raynolds, Laura B.; López-Velásquez, Angela; Olivo Valentín, Laura E. (Reading and Writing, 2017)
Twenty-five 4- and 5-year-old Spanish-speaking English Learners (ELs) were tested in order to compare their English and Spanish performance in two phonological awareness skills: Rhyme awareness (RA) and beginning sound segmentation (BSS). The children had received formal instruction of phonological awareness, with an emphasis on RA and BSS for 1 year and in English only, using the Opening the World of Learning curriculum (Schickedanz & Dickinson, 2005). The results showed that the children scored higher on the English BSS than on the English RA tests (p ¡ .001), even though RA is generally considered to be an earlier developing skill than BSS among English-monolingual children. No significant difference was found between the English BSS and Spanish BSS tests despite the fact that the children had received English-only instruction in these phonological awareness skills for 1 year. The results are discussed in terms of the possible impact of the similarities and differences between the Spanish and English linguistic structures on the learning and cross-linguistic transfer of phonological awareness skills in young Spanish-speaking ELs.
Keywords: Beginning sound segmentation; English-only instruction; Phonological awareness; Prekindergarten; Rhyme awareness; Spanish-speaking English Learners; dept.cur; dept.sed; peer-reviewed